Regulatory mechanism and molecular genetic dissection of rice (Oryza sativa L.) grain size - Yuntao Yan; Xiaoya Zhu; Hui Qi; Haiqing Zhang; Jiwai He (Heliyon, 2024)
With the sharp increase of the global population, adequate food supply is a great challenge. Grain size is an essential determinant of rice yield and quality. It is a typical quantitative trait controlled by multiple genes. In this paper, we summarized the quantitative trait loci (QTL) that have been molecularly characterized and provided a comprehensive summary of the regulation mechanism and genetic pathways of rice grain size. These pathways include the ubiquitin-proteasome system, G-protein, mitogen-activated protein kinase, phytohormone, transcriptional factors, abiotic stress. In addition, we discuss the possible application of advanced molecular biology methods and reasonable breeding strategies, and prospective on the development of high-yielding and high-quality rice varieties using molecular biology techniques.